Influence of absorptive and organizational learning capacities on the relationship between environmental management practices and performance - Zonatto, Vinícius Costa da Silva; Kieling, Débora Londero; Degenhart, Larissa; Rossato, Marivane Vestena; Marquezan, Luiz Henrique Figueira (Revista Gestão Organizacional, 2025)
Purpose: This research analyzes the influence of absorptive capacities and organizational learning on the relationship between environmental management practices and performance. Method/approach: A descriptive study with a quantitative approach (SEM) was conducted with 147 professionals responsible for environmental management in industries in Brazil. Main findings: The results revealed that environmental management practices directly influence absorptive capacity, learning capacity and environmental performance, but not financial performance. Absorptive capacity directly influences learning capacity and financial performance. On the other hand, learning capability directly influences environmental performance. The results revealed that absorptive capacity and learning capacity have mediating effects on the relationship between environmental management practices and performance, which suggests that such capacities enhance the relationship between management practices adopted and environmental performance and financial. Theoretical, practical/social contributions: Based on the results found, the potential contribution of organizational capabilities in the relationship between environmental management practices and performance is recognized. In general, the results indicate that when organizations have higher levels of organizational capability development (absorption and learning), they realize the importance of adopting environmental management practices that contribute to improving their performance (environmental and financial). Originality/relevance: This research expands the evidence from the analysis of the indirect effects of environmental management practices on performance, revealing the roles of absorptive and learning capabilities in this relationship, which highlights the importance of studying organizational capabilities to better understand the effects of management practices on performance.